679. Mass-Scale Post-Hurricane Sheltering of Evacuees From Hurricane Harvey: Infectious Disease Surveillance and Prevention: Dallas County, Texas, 2017. (26th November 2018) - Chung, Wendy; Shim, Kyoo; Blackwell, James; Henderson, Joel; Stocks, Meredith; Richardson, Folasuyi; Hughes, Sonya; Ward, Michelle
Abstract: Background: The record rainfall following Hurricane Harvey's landfall along the Texas coast on August 25, 2017 caused prolonged, widespread flooding, which devastated Houston and areas along the southern Gulf Coast. With shelters in Houston at capacity, residents from adjacent affected regions were evacuated elsewhere, and Dallas received over 3, 800 evacuees at a single convention center shelter. Approaches to infectious disease surveillance and prevention in this mega-shelter setting were assessed and refined during the response. Methods: Teams of epidemiologists and medical students reviewed all clinical records daily from the on-site, 24/7 walk-in medical clinic, which was staffed by local volunteer physicians. Demographic data, chief complaints, and diagnosis for each patient visit were reviewed, and daily aggregate summaries of visits for potential communicable disease symptoms were compiled. An additional infection control team consisting of health department staff and volunteer hospital infection preventionists implemented aggressive infection prevention measures in the shelter and clinic. Results: Of the evacuees registered at this mass-scale shelter, 92% were from counties outside of Houston and 36% were 18 years of age or younger. During the shelter's 23 days of operation, the shelter medical clinic received a cumulative volume of 2, 654 clinic visits from 1, 560 evacuees. The most common reasons for clinic visits included: need for medication refills (27.2%); respiratory symptoms (18.8%); and skin-related complaints (8.6%). Isolated cases of scabies, lice, norovirus, and influenza were confirmed, with no outbreak transmission of communicable diseases reported in the shelter. Conclusion: The need for acute-care medical services and resources at a central shelter location was highlighted by the high proportion (40%) of evacuees seeking care at least once at the shelter medical clinic. The 24/7 accessibility of this on-site medical clinic to evacuees additionally provided a reliable mechanism for daily syndromic surveillance for potential outbreaks of infectious disease in a large shelter. Given the challenges of mass-sheltering and provision of clinical care in non-residential structures, dedicated staffing with infection control expertise was critical in this shelter setting. Disclosures: All authors: No reported disclosures.